Running with whole-body electromyostimulation improves physiological determinants of endurance performance - a randomized control trial - Krause, A.; Walser, N.; Centner, C.; Memmert, D.; da Mota de Moreia, I.; Ritzmann, R. (BMC Sports Science, Medicine and Rehabilitation, 2023)
Background This study aimed to evaluate the physiological and metabolic adaptations to an eight-week running intervention with whole-body electromyostimulation (wbEMS) compared to running without wbEMS.